(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Objective of the Study. To determine the effectiveness of combined therapy including omega-3 fatty acids and IPL compared to monotherapy in military personnel with dry eye syndrome. Material and Methods. The study involved 120 military personnel (240 eyes), divided into three groups. Group 1 received tear substitutes and EPA/DHA, group 2 — only tear substitutes, and group 3 — tear substitutes, EPA/DHA, and IPL. Assessment was conducted using OSDI, Schirmer’s test, Norn’s test, meibography, and measurement of the tear meniscus height over a 12-week period. Results. The most significant improvement across all parameters, including increased tear film break-up time and meibomian gland density, was observed in group 3. Tear film break-up time increased to 9.75±1.16 seconds, meibomian gland density — to 38.2±6.9%, and meibomian gland dysfunction index decreased to 0.74±0.19. These results were statistically significantly different from those in groups 1 and 2 (p<0.05). Conclusion. Combined treatment using EPA/DHA and IPL is more effective in correcting symptoms and morphological disturbances in dry eye syndrome than monotherapy, especially in the presence of meibomian gland dysfunction.